Variables Influencing the Effectiveness of Creatine Supplementation as a Therapeutic Intervention for Sarcopenia - Candow, Darren G.; Forbes, Scott C.; Chilibeck, Philip D.; Cornish, Stephen M.; Antonio, Jose; Kreider, Richard B. (Frontiers in Nutrition, 2019)
Sarcopenia is an age-related muscle condition characterized by a reduction in muscle quantity, force generating capacity and physical performance. Sarcopenia occurs in 8-13% of adults ≥ 60 years of age and can lead to disability, frailty, and various other diseases. Over the past few decades, several leading research groups have focused their efforts on developing strategies and recommendations for attenuating sarcopenia. One potential nutritional intervention for sarcopenia is creatine supplementation. However, research is inconsistent regarding the effectiveness of creatine on aging muscle. The purpose of this perspective paper is to: (1) propose possible reasons for the inconsistent responsiveness to creatine in aging adults, (2) discuss the potential mechanistic actions of creatine on muscle biology, (3) determine whether the timing of creatine supplementation influences aging muscle, (4) evaluate the evidence investigating the effects of creatine with other compounds (protein, conjugated linoleic acid) in aging adults, and (5) provide insight regarding the safety of creatine for aging adults.